Human Rights and Large-Scale Carbon Dioxide Removal: Potential Limits to BECCS and DACCS Deployment - Philipp Günther; Felix Ekardt (Land, 2022)
Negative emissions technologies (NETs) approaches are an essential part of virtually any scenario in which global warming is limited to 1.5 °C in accordance with the Paris Agreement. Discussions often focus on two technologies due to their substantial carbon dioxide (CO2) sequestration potential: bioenergy with carbon capture and storage (BECCS) and direct air carbon capture and storage (DACCS). However, the large-scale deployment of both technologies—especially BECCS—may lead to significant human rights infringements. This paper aims to analyze the impact of both technologies on human rights from the methodological perspective of a legal interpretation of international law. It shows that a large-scale BECCS strategy, which inevitably requires enormous land-use changes, will most likely infringe upon the right to food, the right to water, and the right to a healthy environment. In contrast, large-scale DACCS approaches will likely have a smaller human rights impact, but the energy-intensive process could also infringe upon the right to energy. Balancing these human rights with other freedom rights, e.g., of consumers and enterprises, the paper will further demonstrate that from the perspective of human rights, rapid emission reductions and the minimization of livestock farming—and also less risky nature-based options such as peatland and forest management—should prevail before any large-scale industrial NET strategies.
Keywords: 330; BECCS; DACCS; human rights; international law; Paris agreement; NETs; CDR; climate governance; climate mitigation